Teach with your heart lessons I learned from the Freedom Writers : a memoir - Gruwell, Erin 1969- (Broadway Books, 2007)
In this memoir and call to arms, Erin Gruwell, the dynamic young teacher who nurtured a remarkable group of high school students from Long Beach, California, who called themselves the Freedom Writers, picks up where The Freedom Writers Diary (and the movie The Freedom Writers) end and catches the reader up to where they are today. Teach with Your Heart will include the Freedom Writers' unforgettable trip to Auschwitz, where they met with Holocaust survivors; toured the attic of their beloved Anne Frank (Gruwell had the kids read Anne's Diary in The Freedom Writers Diary); visited Bosnia with their friend Zlata Filipovich, and more. The book also includes what happened with the Freedom Writers as they made their way through college and graduation. Along the way, Gruwell includes lessons for parents and teachers about what she learned from her remarkable band of students.
Keywords: Freedom Writers; High school teaching -- California; High school teachers -- California; Teenagers -- California; High school; Lehrer; Kalifornien